The spatial distribution of salt tolerant bacteria and other soil parameters under different agricultural systems of the Indian Sundarbans - Sreemoyee Mitra; Priyanka Das; Ritabrata Karmakar; Pabitra Banik; Arup Bose (PLoS ONE, 2025)
Salinization is a major contributor to soil degradation and poses a substantial threat to agriculture. In India, approximately 6.73 million hectares of lands are affected by salinity, with the Indian Sundarbans playing a critical role in coastal salinity issues. Our investigation focuses on the agricultural soil in the Indian Sundarbans, shifting away from the previously studied mangrove soil, and delving into its chemical and microbiological characteristics. We aimed to find the spatial variation in soil salinity, nitrogen level, soil organic content, and salt-tolerant bacteria along with any possible effect of bacterial population on soil chemical attributes. This was achieved through soil lab analysis, geo-statistics and analysis of parameters by ArcGIS. Notably, the central Sundarbans exhibits higher salinity levels compared to its eastern and western regions. Salt-tolerant bacteria are more abundant in specific areas, including villages of Bakkhali, Sibrampur, Patharpratima, and certain villages of Sagar Island. While the presence of salt-tolerant bacteria in saline regions is influenced by the types of crops cultivated, most soil characteristics tend to vary primarily due to spatial factors rather than cropping patterns. Further research should focus on the beneficial effects of salt-tolerant bacteria on the Available Nitrogen content in the soil. These findings will aid in understanding microbial growth in saline conditions in the future and benefit crop growth in such challenging environments.